Analisis Usability dan Pengalaman Pengguna Website SMAN 5 Bogor versi Mobile menggunakan MeCUE Questionnaire dan System Usability Scale (SUS) - Muhamad Lukman Nurhakim; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Internet is a medium used to collect information such as news and information related to institution or daily work. One of the media used for dissemination and providing information is sman5kotabogor.sch.id. According to SMAN 5 Bogor IT Team, website never been analyzed or improved since created in 2017. The hypothesis regarding â€œare users satisfied with the website?â€ arises because lack of user experience data. Therefore, it is necessary to analyze user experience and usability of website. To measure user experience, researcher use meCUE questionnaire consisting of 5 modules and 10 aspects. Usability data collection was carried out based on usability metrics from ISO 9241-11 and data was collected by task testing, interviews, and answering system usability scale (SUS) questionnaire. Based on results evaluation of meCUE questionnaire, website have a total value of 1.7 which included in positive category. Analysis also produces negative values â€‹â€‹on intention to use, commitment, and status aspects. In analysis of usability metrics, satisfaction value is 63 or below acceptable and produces normal effectiveness and efficiency values. Improvement according to meCUE questionnaire resulted in 12 improvement (RP) to fix aspects with negative value and improvement based on usability metrics resulted in 9 improvement to improve usability aspects.